Role of Apolipoprotein E in Anxiety - Jacob Raber (Neural Plasticity)
Anxiety is most common among Alzheimer's disease (AD) patients with an age at onset under age 65. Apolipoprotein E4 (apoE4) is a risk factor for developing AD at an earlier age and might contribute to this effect. In mice, apoE plays a role in the regulation of anxiety, which might involve histamine receptor-mediated signaling and steroidogenesis in the adrenal gland. In addition, human apoE isoforms have differential effects on anxiety in adult mice lacking apoE and probable AD patients. Compared to wild-type mice, mice lacking apoE and apoE4 mice showed pathological alterations in the central nucleus of the amygdala, which is involved in regulation of anxiety. ApoE4, but not mice lacking apoE, or apoE3 mice showed impaired dexamethasone suppression of plasma corticosterone. Understanding how apoE modulates measures of anxiety might help the developments of therapeutic targets to reduce or even prevent measures of anxiety in health and in dementing illnesses.